Searching for the key of knowledge: gender studies in Augustine’s correspondence - Nunn, Christopher Alexander (Interdisciplinary forum of digital textual sciences, 2018)
Research about late antique women is often very difficult due to a glaring lack of sources. Letters addressed to women are rare, writings of women even rarer. The correspondence of the bishop of Hippo Regius, Augustine, written between 386 and 430 AD, is no exception. Despite 252 letters written by himself, only 17 are directed to all-female correspondents. Their responses are not extant.